Comparative Performance of Strategies for Conjunctive Use of Fresh and Saline Water to Grow Wheat Crop - Chauhan, C.P.S; Singh, R B; Gupta, S K (Journal of Agricultural Engineering, 2005)
In arid and semi-arid regions, ground water is mainly saline in nature. It is open to question, whether such waters could be exploited to meet the crop water requirement. The experimental evidences generated world over reveal that it could be achieved through conjunctive use. Recently, some conflicting reports have appeared on the relative merits of different modes of conjunctive use i.e. cyclic, switching and mixing modes. A field experiment was conducted during 2001-02 and 2002-03 using low (3.6 dS m¯¹ ) and highly saline water (15 dS m¯¹ ) to show that with appropriate conjunctive mode even highly saline waters could be used to grow wheat crop. It has been shown that substitution of a part of the irrigation water requirement with highly saline water affected the wheat crop less adversely than when all irrigations were given with high salinity water. Yield, as high as 95% of the yield with low saline water could be obtained with cyclic mode (low saline-high saline water cycle) or switching mode (first 2 or 3 irrigations with low saline followed by all irrigations with highly saline water). Both the strategies were equally effective provided low saline water is applied at pre-sowing and/or initial growth stages of the wheat crop. At the same salt load, the mixing mode tried in this study could also give more than 90 % of the yield obtained with low saline water. The yield differences under the three best treatments (one each under the three strategies) with equal salt load were non-significant. The yield in the case of cyclic mode (highly saline-low saline) or switching mode (highly saline followed by low saline) was less than their counterparts (low-high saline cycle or switching) as well as the mixing mode. Apparently, salt stress at germination and initial establishment stages affected the crop performance. If it is so, the yield under mixing mode could be improved provided mixing ratio is varied with stage of growth although total salt load could be the same. Therefore, the conclusion regarding mixing mode drawn from this study should be treated as temporary till more results are obtained in future studies. It emerges that one can manage the matric and osmotic stresses with conjunctive use to get high yields and ensure sustainability of irrigated agriculture. For developing an effective strategy crop characteristics, water qualities in hand and the past experiences should play an important role.